Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita Siswa Kelas 4 Sekolah Dasar - Kurniawati, Ayu (ISLAMIKA, 2024)
This study aims to identify and analyze the factors causing students' difficulties in solving mathematical word problems. The research employs a descriptive qualitative approach, with data collection methods including observation, interviews, and documentation. Observations were conducted to understand the context of students' learning environments, while interviews were used to explore in depth the factors contributing to difficulties in learning mathematics. The findings indicate that there are three main types of errors frequently made by students when solving mathematical word problems: (1) Inability to properly understand and interpret the problem, (2) Limited understanding of mathematical concepts, making it difficult for students to determine the correct formulas, and (3) Errors in applying the correct formulas. These learning difficulties are caused by two main factors: (1) Internal factors, such as low interest and motivation to learn, and (2) External factors, such as an unsupportive learning environment. Efforts to overcome these difficulties include increasing the active role of parents in fostering children's interest and study habits, as well as the importance of schools providing a conducive and enjoyable learning environment. Additionally, teachers need to develop more interactive and engaging teaching methods for students.